2016
DOI: 10.1093/imrn/rnw223
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Bilinear Restriction Estimates for General Hypersurfaces and the Role of the Shape Operator

Abstract: Abstract. It is known that under some transversality and curvature assumptions on the hypersurfaces involved, the bilinear restriction estimate holds true with better exponents than what would trivially follow from the corresponding linear estimates. This subject was extensively studied for conic and parabolic surfaces with sharp results proved by Wolff [28] and Tao [23, 24], and with later generalizations [16,17,8,20]. In this paper we provide a unified theory for general hypersurfaces and clarify the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Recall also from (1.9) that Γ φ z1 (z 1 , z 2 ) = 2(y 2 − y 1 )τ z1 (z 1 , z 2 ) and Γ φ z2 (z 1 , z 2 ) = 2(y 2 − y 1 )τ z2 (z 1 , z 2 ). Thus, by Lemma 4.1 and (2.11), we have that for z 1…”
Section: )mentioning
confidence: 82%
See 1 more Smart Citation
“…Recall also from (1.9) that Γ φ z1 (z 1 , z 2 ) = 2(y 2 − y 1 )τ z1 (z 1 , z 2 ) and Γ φ z2 (z 1 , z 2 ) = 2(y 2 − y 1 )τ z2 (z 1 , z 2 ). Thus, by Lemma 4.1 and (2.11), we have that for z 1…”
Section: )mentioning
confidence: 82%
“…For more details on this condition, we refer to the corresponding literature dealing with bilinear estimates, for instance [1,21,22,35]. In particular, according to [21, Theorem 1.1], transversality is achieved if the modulus of the following quantity…”
Section: Introductionmentioning
confidence: 99%
“…In particular, if Φ 1 and Φ 2 are elliptic phases with curvature Financial support by the DFG through the CRC "Taming uncertainty and profiting from randomness and low regularity in analysis, stochastics and their applications" is acknowledged. 1 at different scales, then (1.1) was obtained by Stovall [20] with an almost sharp dependence on the scale. If n = 2, and Φ 1 = Φ 2 = ξ m1 1 + ξ m2 2 are surfaces of finite type with rectangular sets Λ j ⊂ {0 < ξ 1 , ξ 2 < 1}, then the essentially optimal dependence of the constant C on the rectangles Λ j and parameters m j 2 has been obtained in recent work of Buschenhenke-Müller-Vargas [3].…”
Section: Introductionmentioning
confidence: 89%
“…On the other hand, in the case of the Schrödinger equation, Φ 1 = Φ 2 = |ξ| 2 , if Λ 1 is a ball of radius 1, and Λ 2 is a ball of radius λ 1 such that the sets Λ 1 and Λ 2 are separated by a distance λ, then work of Tao [22] shows that for q = r > n+3 n+1 the bilinear estimate (1.1) holds with C ≈ λ 1 r −1+ǫ for every ǫ > 0. In the case of general phases which are both at unit scale, under suitable transversality and curvature assumptions, and Bejenaru [1] have shown that (1.1) again holds in the non-endpoint range q = r > n+3 n+1 . For general phases which are not at unit scale, only in certain special cases is the dependence of C in (1.1) on the phases Φ j and sets Λ j known.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation